Novel Attacks on Spread-Spectrum Fingerprinting. (17th August 2008) - Schaathun Schaathun, Hans Georg Hans Georg
Abstract : Spread-spectrum watermarking is generally considered to be robust against collusion attacks, and thereby suitable for digital fingerprinting. We have previously introduced the minority extreme attack (IWDW' 07), and showed that it is effective against orthogonal fingerprints. In this paper, we show that it is also effective against random Gaussian fingerprint. Furthermore, we develop new randomised attacks which counter the effect of the decoder preprocessing of Zhao et al.